GRAPHIC DESIGN IN THE ERA OF INDUSTRY 4.0: REFRAMING OF COMPETENCE IN THE CONTEXT OF THE LATEST CHALLENGES - Геренко , Софія (Art and Design, 2024)
Goal. Аn analysis and reflection on reframing the competence of a graphic designer in the era of Industry 4.0, based on the latest trends and challenges in the field. Methodology. Methods of system-structural analysis, synthesis, and generalization were used; competence and problematic-diagnostic approaches were applied, and also the analysis of vectors and stages of digital transformation. Results. The role of Industry 4.0 technologies was studied in the transformation of the graphic designer’s competence structure in the first quarter of the XXI century. The attention was concentrated on the necessity of reframing (revision, rethinking) graphs competence under the influence of new digital technologies, which is a requirement of the time. The problem of “qualified specialists versus freelancers” in the industry was identified and described. The advantages and disadvantages of using artificial intelligence in the work of a new generation graphic designer were analyzed. Scientific novelty is in a systematic analysis of the problem of reframing the competence and improving the qualifications of a graphic designer in connection with the latest logic of digital development: awareness of the need for change and the fact that the future of graphic design lies in the harmonious coexistence of human creativity and AI, in which Industry 4.0 technologies will act as a “creative partner” and help expand the boundaries of visual communication and artistic expression. Practical significance of the research is to highlight the current trend in the field of graphic design, where creative experiments with advanced digital technologies are ongoing, which, in turn, initiates a reframing of the competence of a graphic designer and changes in educational practices and design thinking: an emphasis on professional software in the industry based on AI (InDesign, Illustrator), computer knowledge and skills of creative, critical and strategic thinking.